1999
DOI: 10.1021/np980324p
|View full text |Cite
|
Sign up to set email alerts
|

Two New Bromophenols from the Red AlgaOdonthalia corymbifera

Abstract: Two novel bromophenols (1 and 2) were isolated from an extract of a red alga, Odonthalia corymbifera, together with a known bromophenol (3). The novel bromophenols were determined as 4-bromo-2, 3-dihydroxy-6-hydroxymethylphenyl 2, 5-dibromo-6-hydroxy-3-hydroxymethylphenyl ether (1) and bis(2, 3-dibromo-4,5-dihydroxybenzyl) ether (2), from spectroscopic evidence. Compounds 1-3 were found to be inactivators of alpha-glucosidase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
80
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 15 publications
3
80
0
Order By: Relevance
“…Initial chemical characterization of the polyphenolics using NMR suggests that phlorotannins structures of high molecular mass are responsible for the a-glucosidase inhibitory activity (results not shown). In addition, structural analysis did not uncover the presence of any brominated compounds so the polyphenols are distinct from the a-glucosidase-inhibiting bromophenols of red seaweed reported by (Kurihara et al 1999).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Initial chemical characterization of the polyphenolics using NMR suggests that phlorotannins structures of high molecular mass are responsible for the a-glucosidase inhibitory activity (results not shown). In addition, structural analysis did not uncover the presence of any brominated compounds so the polyphenols are distinct from the a-glucosidase-inhibiting bromophenols of red seaweed reported by (Kurihara et al 1999).…”
Section: Discussionmentioning
confidence: 79%
“…Inhibition of a-glucosidase by acarbose (Precose) or miglitol (Glycet) delays the absorption of glucose from the small intestine (Bischoff 1994;Lebovitz 1997) and, as demonstrated in the STOP-NIDDM trial (Chiasson et al 2002), is an effective antidiabetic therapeutic approach. Research has also revealed that a variety of food materials contain compounds that inhibit a-glucosidase including fermented soybean (Fujita et al 2001), purple sweet potato (Matsui et al 2001), propolis (Matsui et al 2004), leaf tea (Youn et al 2004), fish protein hydrolysates (Matsui et al 1999) and seaweed (Kurihara et al 1999). Extracts prepared from these sources effectively blunt the appearance of glucose in blood after carbohydrate tolerance testing in animals and, in the case of fermented soybean extract, in a humans (Fujita et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous chemical studies on some species of this family have more than thirty monoaryl and diaryl bromophenols (Zhao et al, 2004), which exhibit antibacterial, antioxidant, a-glucosidase inhibitory, and anti-inflammatory activities. N. aculeata have also several bromophenols (Phillips and Carlyle, 1981;Xu et al, 2003) and the chemicals exhited α-glucosidase inhibitors used in oral anti-diabetic drugs for diabetes mellitus type 2 (Kurihara et al, 1999;Lim et al, 2006;Xu et al, 2003). Thus, in the extract of N. aculeata, the potential candidate chemical showing cytoprotective effects on pancreatic βcells seem to be a kind of phenols such as bromophenols but further studies are needed to determine which components of N. aculeata mediate cyoprotective effects in pancreatic β cells.…”
Section: Discussionmentioning
confidence: 99%
“…The red alga, Neorhodomela aculeata (Perestenko) Masuda has been used by the Chinese for centuries for the treatment of certain illnesses (Li et al, 1994). The methanolic extract of N. aculeata and a number of bromophenol metabolites isolated from their methanolic extract have antibacterial, antioxidant, and anti-inflammatory activities (Kurihara et al, 1999;Lim et al, 2006). However, no pharmacological properties of N. aculeata have been reported as antioxidant and anti-inflammatory agents in the pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…19) The methanolic extract of N. aculeata and a number of bromophenol metabolites isolated from their methanolic extract have antibacterial activities. 20) However, no pharmacological properties of N. aculeata have been reported as antioxidant and anti-inflammatory agents in the brain. Therefore, these experiments were conducted to evaluate the properties of the methanolic extract of N. aculeata with neuronal cells and microglial cells.…”
mentioning
confidence: 99%